Respostas
respondido por:
1
(n-5)^2 = primeiro ao quadrado - 2 vezes o primeiro vezes o segundo + o segundo ao quadrado, logo
n^2-10n+25
n^2-10n+25
respondido por:
2
Resolução:
(- 5 + n)² = (- 5 + n).(-5 + n) = 25 - 5n - 5n + n² = 25 - 10n + n² ou
n² - 10n + 25
bons estudos:
(- 5 + n)² = (- 5 + n).(-5 + n) = 25 - 5n - 5n + n² = 25 - 10n + n² ou
n² - 10n + 25
bons estudos:
leli14:
entra em meu perfil e me ajuda jotao
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás